2016
DOI: 10.14740/jocmr2589w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sympathetic Skin Response to the Dry Needling Treatment in Female Myofascial Pain Syndrome Patients

Abstract: BackgroundThe aim of this study was to evaluate sympathetic nervous system (SNS) activity following dry needling (DN) treatment, by using the sympathetic skin response (SSR) method in female patients diagnosed with myofascial pain syndrome (MPS).MethodsTwenty-nine MPS patients with trapezius muscle pain and 31 healthy subjects were included in this study. During a single treatment session, DN treatment was applied into trigger points, for a duration of 10 minutes. Healthy patients were subjected to SSR in week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…In another study, the application of DN resulted in changes in the ANS, with subjects experiencing an increase in blood flow, both in skin and the muscle [ 51 ]. In contrast, another study evaluating the effects of DN on skin sympathetic activity found no significant changes after DN in a group of healthy subjects, but did find changes in skin sympathetic activity in the patient group [ 52 ]. In a recent study of healthy subjects in which acupuncture to tendons was applied, a change in local blood flow was observed, which was controlled by the SNS, but this was not related to heart rate [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the application of DN resulted in changes in the ANS, with subjects experiencing an increase in blood flow, both in skin and the muscle [ 51 ]. In contrast, another study evaluating the effects of DN on skin sympathetic activity found no significant changes after DN in a group of healthy subjects, but did find changes in skin sympathetic activity in the patient group [ 52 ]. In a recent study of healthy subjects in which acupuncture to tendons was applied, a change in local blood flow was observed, which was controlled by the SNS, but this was not related to heart rate [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hyperactivity of the sympathetic nervous system plays an important role in the pathophysiology of myofascial pain syndrome [ 24 , 25 ]. Some studies have indicated that self-massage combined with home exercise can improve parasympathetic activity [ 26 ], and dry needling treatment can effectively reduce the sympathetic skin response [ 27 ]. Both the above interventions can help improve myofascial pain syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular functional outcome tools in the C region were the NDI, followed by the SF-36. Although studies investigating only physiological responses were excluded, one study used sympathetic skin response along with other outcomes [61]. Some outcomes such as NHP, BDI and DHI were used in four studies or fewer.…”
Section: Discussionmentioning
confidence: 99%